Allostatic Load, Mobility Disability, and Viral Effects in Cancer: A Structural Equation Model - Hollar, David W. (Cancer investigation, 2022)
A growing number of cancers have been linked to specific oncogenic viruses and physiological stress. Recently, two separate studies linked mobility limitations to allostatic load and four major cancer types. The objective of this study was to determine if cancer occurrence regresses on three latent domains of Allostatic Load, Level of Physical Functioning (i.e., Mobility Disability), and Viral Exposure. We compared several structural equation models using adult participant (n = 17,969) data from three National Health and Nutrition Examination Survey (NHANES) periods. The primary two-level model with three exogenous latent factors and a single Cancer endogenous latent factor demonstrated a strong fit (GFI = 0.948, RMSEA = 0.024), and the model had a non-significant Chi-Square indicative of a strong model. What is already known on this subject Allostatic load represents how the body responds to physiological stress and is associated with increased morbidity/mortality, including cancers. Viruses are the causative agents of 15-20% of cancers and can be stress activated. People with mobility limitations experience significantly higher allostatic loads and secondary health conditions, and one recent study indicates a heightened risk for certain cancers. What this study adds This study is original in its testing of a conceptual model that links together cancer outcomes with latent factors/variables including disability/mobility limitations, allostatic load, and viral exposure. The study indicates that there might be important associations between allostatic load, disability burden, and viral exposure/activation on the occurrence of cancer. The research suggests the need for stress reduction, preventative health interventions, and additional supports for people with disabilities and their caregivers.